NEW INSIGHTS INTO ANTIOXIDANT AND ANTIVIRAL ACTIVITIES OF TWO WILD MEDICINAL PLANTS: ACHILLEA FRAGRANTISSIMA AND NITRARIA RETUSA - AMAL A. MOHAMED,; SAMI I. ALI,; FAROUK K. EL-BAZ,; WALED M. EL-SENOUSY, (International Journal of Pharma and Bio Sciences, 2015)
The present work was undertaken to evaluate the polyphenolic content, antioxidant and antiviral properties of two wild medicinal plants; Achillea fragrantissima and Nitraria retusa. The crude extracts of both plants were prepared using methanol and ethyl acetate solvents. Generally, total phenolic content ranged from 0.31 to 15.05 mg gallic acid equivalents /g dw, where total flavonoid content varied from 0.23 to 9.30 mg quercetin equivalents /g dw. Methanolic extract of A. fragrantissima showed the highest phenolic and flavonoid content compared to N. retusa. However, methanolic extract of N. retusa showed strong antioxidant activity (IC50= 68 µg ml-1) in the DPPH free radical scavenging assay. Additionally, both A. fragrantissima and N. retusa extracts showed antiviral activity against Rotavirus Wa, Adenovirus type 7 and Coxsackievirus B4. Further research is needed to elucidate the active constituents of both plants which may be useful in the development of new and effective antioxidant and antiviral agents.